The postural status of female first league basketball players - Dordevic, S.; Vidojevic, M.; Cokic, M.; Milenkovic, M.; Stankovic, R. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The aim of this research was to determine the postural status of first league female basketball players. The sample of participants consisted of 12 elite senior basketball players who had been involved in a training program for more than eight years. To evaluate the postural status of the spinal column in the frontal and sagittal plane, as well as to evaluate the postural status of the legs and feet in the frontal plane, a special measuring instrument was used (Formetric 4D System, Diers, Germany). To determine the differences in the prevalence of deformities and normal posture, the Chi square test was used. The results indicated that the prevalence of physical deformities of the spinal column are found in the following percentages: kyphosis (66.7%), lordosis (100%) and scoliosis (91.7%) while the prevalence of the percentage of leg and arch deformity was: knock-knees (8,3%), bowlegs (91.7%) and flat feet (58.3%). Based on the obtained information on their postural status, we can conclude that frequent control and monitoring of postural status among elite female athletes is necessary. In addition, the constant strengthening of both sides of the body is needed, especially in the case of sports where the specific nature of the technical elements is tied to the dominant side of the body.